Building a Salutogenic School Ecosystem: Stakeholder Engagement in Health Promotion throught School Health Program (UKS) - Zuhrah, Hana Mufidatuz; Noviyanti, Tausyiah Rohmah; Siwidati, Anggit Wirama; Firdausya, Farah Amalia; Sulistyowati, Muji (Universitas Airlangga, 2026)
Background: Indonesia's School Health Program (UKS) is a key strategy for promoting student well-being. However, in Sukoharjo Regency, health service coverage for elementary students (52.0%) lags behind the Central Java provincial average (60.9%). Research highlights school and health center policy support as a critical driver for school health promotion. The involvement of health and education staff, teachers, parents, and community figures is a core element of the WHO's Health Promoting School (HPS) framework (SEARO, 2003), yet it is not formally integrated into the standard Indonesian UKS (TRIAS UKS) indicators. Objective This study aims to identify the application of this stakeholder involvement element in the implementation of UKS across all junior high schools in Sukoharjo District. Methods: This research employs an evaluative mixed-method design conducted in 10 junior high schools (JHS) in the Sukoharjo District and involves 25 informants. Results: All schools involved parents through school committees, although their engagement in UKS activities varied. Community participation included collaborations with health centers and the Youth Red Cross. Local businesses supported school health initiatives through menstrual hygiene programs and industrial visits, while community organizations facilitated the dissemination of local health information. Schools also partnered with fire departments for first-aid and disaster-preparedness activities, as well as with local clinics for health outreach and vendor mediation. Conclusion: Stakeholder involvement reflects the salutogenic principle of fostering resources that enable schools to build a health-supportive ecosystem. Strengthening and institutionalizing this multi-stakeholder collaboration within UKS implementation is essential for enhancing student resilience, improving health literacy, and ensuring the sustainability of school-based health promotion.